Genetic background modulates phenotypic expressivity in OPA1 mutated mice, relevance to DOA pathogenesis - Atamena, Djamaa; Gurram, Venu; Petsophonsakul, Petnoï; Khosrobakhsh, Farnoosh; Arrázola, Macarena S.; Botella, Marlène; Wissinger, Bernd; Szelechowski, Marion; Belenguer, Pascale (Frontiers in Molecular Neuroscience, 2023)
Dominant optic atrophy (DOA) is mainly caused by OPA1 mutations and is characterized by the degeneration of retinal ganglion cells (RGCs), whose axons form the optic nerve. The penetrance of DOA is incomplete and the disease is marked by highly variable expressivity, ranging from asymptomatic patients to some who are totally blind or who suffer from multisystemic effects. No clear genotype–phenotype correlation has been established to date. Taken together, these observations point toward the existence of modifying genetic and/or environmental factors that modulate disease severity. Here, we investigated the influence of genetic background on DOA expressivity by switching the previously described DOA mouse model bearing the c.1065 + 5G → A Opa1 mutation from mixed C3H; C57BL/6 J to a pure C57BL/6 J background. We no longer observed retinal and optic nerve abnormalities; the findings indicated no degeneration, but rather a sex-dependent negative effect on RGC connectivity. This highlights the fact that RGC synaptic alteration might precede neuronal death, as has been proposed in other neurodegenerative diseases, providing new clinical considerations for early diagnosis as well as a new therapeutic window for DOA. Furthermore, our results demonstrate the importance of secondary genetic factors in the variability of DOA expressivity and offer a model for screening for aggravating environmental and genetic factors.